Increased risk of mortality by fibrosis stage in nonalcoholic fatty liver disease: Systematic review and meta‐analysis. Issue 5 (31st March 2017) - Dulai, Parambir S.; Singh, Siddharth; Patel, Janki; Soni, Meera; Prokop, Larry J.; Younossi, Zobair; Sebastiani, Giada; Ekstedt, Mattias; Hagstrom, Hannes; Nasr, Patrik; Stal, Per; Wong, Vincent Wai‐Sun; et al.
Abstract : Liver fibrosis is the most important predictor of mortality in nonalcoholic fatty liver disease (NAFLD). Quantitative risk of mortality by fibrosis stage has not been systematically evaluated. We aimed to quantify the fibrosis stage–specific risk of all‐cause and liver‐related mortality in NAFLD. Through a systematic review and meta‐analysis, we identified five adult NAFLD cohort studies reporting fibrosis stage–specific mortality (0‐4). Using fibrosis stage 0 as a reference population, fibrosis stage–specific mortality rate ratios (MRRs) with 95% confidence intervals (CIs) for all‐cause and liver‐related mortality were estimated. The study is reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement. Included were 1, 495 NAFLD patients with 17, 452 patient years of follow‐up. Compared to NAFLD patients with no fibrosis (stage 0), NAFLD patients with fibrosis were at an increased risk for all‐cause mortality, and this risk increased with increases in the stage of fibrosis: stage 1, MRR = 1.58 (95% CI 1.19‐2.11); stage 2, MRR = 2.52 (95% CI 1.85‐3.42); stage 3, MRR = 3.48 (95% CI 2.51‐4.83); and stage 4, MRR = 6.40 (95% CI 4.11‐9.95). The results were more pronounced as the risk of liver‐related mortality increased exponentially with each increase in the stage of fibrosis: stage 1, MRR = 1.41 (95% CI 0.17‐11.95); stage 2, MRR = 9.57 (95% CI 1.67‐54.93); stage 3, MRR = 16.69 (95% CI 2.92‐95.36); and stage 4, MRR = 42.30 (95% CI 3.51‐510.34). Limitations of the study include an inability to adjust for comorbid conditions or demographics known to impact fibrosis progression in NAFLD and the inclusion of patients with simple steatosis and nonalcoholic steatohepatitis without fibrosis in the reference comparison group. Conclusion: The risk of liver‐related mortality increases exponentially with increase in fibrosis stage; these data have important implications in assessing the utility of each stage and benefits of regression of fibrosis from one stage to another. (Hepatology 2017;65:1557‐1565).